The Latin-American Union and the LAT - Copertari, Luis F. (Advances in Social Sciences Research Journal, 2020)
Objective. To support the creation of a Latin-American Union with the creation of the Latin-American peso (LAT) as the common currency. Methodology. Analysis and synthesis using induction and deduction proposing theory and reviewing its validity. Results. The LAT can be used as a robust enough currency. Limitations. The study was carried out only for the three main Latin-American Union candidates: Argentina, Brazil and Mexico. Originality. The ideas proposed here are original in the way the LAT is meant to function. Conclusions. The LAT promises to be a good option for stabilizing Latin-America and promote its regional development.